Survey on Comparative Study of Online vs. Offline Buying Behavior of Consumer for Grocery Product in Surat - Mohit Rakholiya; Rensi Ramani; Jignesh Vidani (Journal of Advanced Research in Economics and Business Management, 2024)
This research delves into the multifaceted dynamics of consumer behavior in the grocery shopping landscape of Surat, Gujarat, where traditional brick-and-mortar stores coexist with the burgeoning realm of online platforms. The study investigates the preferences of different age groups, exploring factors such as proximity to home, product quality, personal interactions with store staff, the ability to inspect products, and the allure of special discounts. Focusing on two prominent players, JioMart and DMart, the research aims to provide a comprehensive understanding of the factors shaping consumer choices in this dynamic market. The literature review explores previous studies on online shopping intentions, the impact of demographic variables on online shopping in India, and the influence of factors like monthly income, gender, and peer influence on consumer behavior for apparel. Highlighting the younger population’s central role in online shopping, the review emphasizes the need for a nuanced understanding of consumer behavior, considering various demographic factors. The research objectives center around conducting a comparative study of online vs. offline buying behavior for grocery products in Surat. The research design involves a descriptive approach with non-probability convenient sampling, encompassing 156 respondents in the Surat area. Primary data is collected through a Google Form questionnaire, and the analysis is performed using MS Excel and SPSS. The research identifies a notable gap in existing studies, emphasizing the need to explore factors beyond convenience and digital marketing impact, such as cultural influences, trust dynamics, and specific preferences of urban versus suburban consumers in the grocery retail context.